Is drowning a mere matter of resuscitation?. (August 2018) - Szpilman, David; de Barros Oliveira, Rafael; Mocellin, Onir; Webber, Jonathon
Abstract: International data severely underestimates actual drowning numbers. Almost all victims are able to help themselves or are rescued in time. This study aims to report the occurrence of Drowning Chain of Survival actions and resuscitations needed in a fully operational lifeguard service. Methodology: Data was collected from Dec-2009 to Mar-2015 by lifeguards at a 6km-long beach in Brazil. The Drowning Chain of Survival links were summarized into 3 main action-response sections: Prevention; rescue; and provide care. Rescues were classified by severity. Results: Lifeguards reported 1, 565, 699 actions during the study period. Preventative actions comprised 1, 563, 300(99.8%) and 2044 (0.1%) involved recognizing a person in stress/distress and rescuing them. Of those requiring rescue, 355(0.02%) needed medical assistance due to respiratory symptoms, isolated respiratory arrest, or cardiopulmonary arrest. Those cases were classified by severity as: Grade 1 = 234(65.9%), grade 2 = 78(22%), grade 3 = 22(6.2%), grade 4 = 7(2%), grade 5 = 4(1.1%), and Grade 6 = 10(2.8%). From all 2044 rescues, 14(0.7%) were grade 5 and 6 and needed respiratory or cardiorespiratory resuscitation. An estimative incident rate for each day at a lifeguarded beach revealed: 1 rescue for every 4.227 beach attendances, 1 drowning for every 24, 338 beach attendances, and 1 instance of CPR being performed for every 617, 142 beach attendances. The prevalent misconception that majority of drowning require resuscitation is perpetuated by the media and publishers. We are only just seeing the tip of the iceberg and urgently need to look at the problem in its entirety. Considering all the intervention undertaken by lifeguards in a fully operational system, the incidence of resuscitation being performed is only one in every 112, 000 lifeguarding actions (0.0009%).